2005
DOI: 10.5483/bmbrep.2005.38.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cu/Zn SOD Protein Is Suppressed in hsp 70.1 Knockout Mice

Abstract: Heat shock proteins (HSPs) are known to protect cells from oxidative stress and other types of injuries. We previously reported the neuroprotective effect of HSP70 following cerebral ischemia and reperfusion using hsp 70.1 knockout (KO) mice. However, the precise role of HSP70 in neuroprotection has not been established yet. The purpose of this study was to investigate the relationship between HSP70 and antioxidant enzymes using hsp 70.1 KO mice. The activities of both SOD-1 and SOD-2 were significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…GPx and GR are both the major regulating enzymes in the glutathione antioxidant system. Superoxide dismutase activities were significantly decreased in hsp 70.1 knock-out mice than in the wild-type littermates (Choi et al 2005). The present study showed that hydrogen peroxide-induced superoxide accumulation is decreased by heat-shock response.…”
Section: Discussionmentioning
confidence: 93%
“…GPx and GR are both the major regulating enzymes in the glutathione antioxidant system. Superoxide dismutase activities were significantly decreased in hsp 70.1 knock-out mice than in the wild-type littermates (Choi et al 2005). The present study showed that hydrogen peroxide-induced superoxide accumulation is decreased by heat-shock response.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the higher post-ischemic expression of HSP-27 and -72 in WHWadministered mice may account for the reduced inflammatory responses, disruption of cytoskeleton in the tubular epithelium, and oxidative stress (Park et al, 2001Vayssier and Polla, 1998;Kelly, 2005;Huot et al, 1996). Choi et al found that deletion of hsp 70.1 gene in mice decreased the activity and expression of both CuZnSOD and MnSOD, indicating that HSP-70 is involved in regulation of oxidative stress (Choi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Newly synthesized proteins in the cytosol destined to mitochondria interact with chaperones in the cytosol, which include HSP90 and HSP70 (18,27,38,45,51). Previous studies have shown that the activity of both SOD-1 and SOD-2 was significantly decreased in HSP70.1 knockout mice compared with the wildtype littermates (17). However, the nature of this interaction between SOD-2 and its chaperone remains unknown.…”
mentioning
confidence: 94%